Bringing the shovel down - Gay, Ross, 1974- (Pitt poetry series., 2011)
Bringing the Shovel Down is a re-imagination of the violent mythologies of state and power. ""These poems speak out of a global consciousness as well as an individual wisdom that is bright with pity, terror, and rage, and which asks the reader to realize that she is not alone--that the grief he carries is not just his own. Gay is a poet of conscience, who echoes Tomas Transtromer's 'We do not surrender. But want peace.'""--Jean Valentine ""Ross Gay is some kind of brilliant latter-day troubadour whose poetry is shaped not only by yearning but also play and scrutiny, melancholy and intensity.